Difficulties Faced by Science Teachers in Selected Public Schools in Kuwait: A Descriptive Study - Al-Kandari, Ebrahim Abdullah; Ramdane, Tahraoui; Nordin, Mohamad Sahari (IIUM Journal of Educational Studies, 2019)
There are numerous difficulties associating with the teaching process in the secondary public schools in Kuwait. The aim of the study is to determine some of the difficulties facing science teachers in secondary schools of Mubarak AL Kabeer governorate in Kuwait. The difficulties encountered by science teachers in secondary schools were examined under these issues: curriculum objectives, student assessment system, school management and science laboratory. Seventy-seven science teachers were chosen randomly from secondary schools in Mubarak AL Kabeer governorate. A structured pretested self-administered questionnaire in Arabic was used to collect data for this study. The analyzed data indicated that both male and female science teachers have difficulties with the curriculum objectives, student assessment system, school management and science laboratory. This study suggested number of recommendations for teachers and administrators in secondary schools